The influence of carbohydrate ingestion on peripheral and central fatigue during exercise in hypoxia: A narrative review - Paris, H. L.; Sinai, E. C.; Shei, R.-J.; Keller, A. M.; Mickleborough, T. D. (European Journal of Sport Science, 2021)
Hypoxia impairs aerobic performance by accelerating fatiguing processes. These processes may originate from sites either distal (peripheral) or proximal (central) to the neuromuscular junction, though these are not mutually exclusive. Peripheral mechanisms include decrements in muscle glycogen or fluctuations in intramuscular metabolites, whereas central responses commonly refer to reductions in central motor drive elicited by alterations in blood glucose and neurotransmitter concentrations as well as arterial hypoxemia. Hypoxia may accelerate both peripheral and central pathways of fatigue, with the level of hypoxia strongly dictating the degree and primary locus of impairment. As more people journey to hypoxic settings for work and recreation, developing strategies to improve work capacity in these environments becomes increasingly relevant. Given that sea level performance improves with nutritional interventions such as carbohydrate (CHO) ingestion, a similar strategy may prove effective in delaying fatigue in hypoxia, particularly considering how the metabolic pathways enhanced with CHO supplementation overlap the fatiguing pathways upregulated in hypoxia. Many questions regarding the relationship between CHO, hypoxia, and fatigue remain unanswered, including specifics on when to ingest, what to ingest, and how varying altitudes influence supplementation effectiveness. Therefore, the purpose of this narrative review is to examine the peripheral and central mechanisms contributing to fatigue during aerobic exercise at varying degrees of hypoxia and to assess the role of CHO ingestion in attenuating fatigue onset.